2011
DOI: 10.1108/09526861111174215
|View full text |Cite
|
Sign up to set email alerts
|

Measuring, evaluating and improving hospital quality parameters/dimensions – an integrated healthcare quality approach

Abstract: The paper describes a new instrument and method. The study assures relevance, validity and reliability, while being explicitly change-oriented. The authors argue that patient satisfaction is a cumulative construct, summing satisfaction as five different qualities (5Qs): object; processes; infrastructure; interaction and atmosphere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 8 publications
0
21
0
Order By: Relevance
“…A research conducted by Dingley et al (2008), found that 40 percent of the communication time between nurses and physicians was problematic time. Many studies reveals that life-long learning, training, good work environment at hospitals, nurse involvement in decision making and positive doctor-nurse relations are positively correlated with improved patient outcomes, patient trust and satisfaction (Aiken et al, 2012;Zineldin, 2006;Zineldin et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A research conducted by Dingley et al (2008), found that 40 percent of the communication time between nurses and physicians was problematic time. Many studies reveals that life-long learning, training, good work environment at hospitals, nurse involvement in decision making and positive doctor-nurse relations are positively correlated with improved patient outcomes, patient trust and satisfaction (Aiken et al, 2012;Zineldin, 2006;Zineldin et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The 5Q items covers human and non-human items such as doctors and nurses professional treatment, sense of well-being at the wards, physical appearance, the relationship of health services to a specific patient complaint or diagnosis, admission and waiting times, personal behavior, communication, trust and other safety measures. Zineldin et al (2011) found that sense of well-being and sense of security from physical harm in hospital, nurses' responsiveness patient needs, doctors skills and the explanation about patient treatment 83 Physiciansnurses performance are some most important factor of patients perception of quality, safety and satisfaction for the Turkish and Kazakhstan patients.…”
Section: Introductionmentioning
confidence: 99%
“…Patient safety and patient satisfaction respond equally to increased activity and nursing performance. Zineldin et al (2011). Therefore in this study, the fifth hypothesis is: H5: Patient safety has a positive effect on patient satisfaction…”
Section: Patient Safetymentioning
confidence: 89%
“…Overall, patient satisfaction is affected by the quality of the service delivered, the underlying systems and processes, infrastructure, interaction with staff and the general atmosphere. [2021] For clinical services, one of the major barriers for the uptake of eye care services is the “fear of surgery,” which is tied to the clinical outcome of cataract surgery. [2223] Therefore, clinical outcomes are regularly monitored.…”
Section: Key Factors For the Success Of The Modelmentioning
confidence: 99%